2016
DOI: 10.3400/avd.oa.15-00088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of the Soleal Vein and Related Drainage Veins, in Calf Vein Thrombosis in Autopsy Cases with Massive Pulmonary Thromboembolism

Abstract: Objective: To clarify the histopathological characteristics of deep vein thrombosis (DVT) resulting in lethal pulmonary thromboembolism (PE). Subjects and Methods:We investigated 100 autopsy cases of PE from limb DVT. The distribution and chronology of DVT in each deep venous segment were examined. Venous segments were classified into three groups: iliofemoral vein, popliteal vein and calf vein (CV). The CV was subdivided into two subgroups, drainage veins of the soleal vein (SV) and non drainage veins of SV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
0
36
2
1
Order By: Relevance
“…However, we still emphasized distal imaging because lethal thromboemboli may occur in proximal veins as a result of proximal propagation from calf DVT. 46 In addition, isolated distal DVT was significantly more often associated with 47 However, no differences were observed in recent surgery or hospital admission between the DVTpositive and -negative groups in our study. Overdiagnosis may also be considered, but each ultrasonographic examination positive for DVT was confirmed by at least one other investigator, including at least one physician.…”
Section: High Incidence Of Dvt In Temporary Housingcontrasting
confidence: 51%
See 1 more Smart Citation
“…However, we still emphasized distal imaging because lethal thromboemboli may occur in proximal veins as a result of proximal propagation from calf DVT. 46 In addition, isolated distal DVT was significantly more often associated with 47 However, no differences were observed in recent surgery or hospital admission between the DVTpositive and -negative groups in our study. Overdiagnosis may also be considered, but each ultrasonographic examination positive for DVT was confirmed by at least one other investigator, including at least one physician.…”
Section: High Incidence Of Dvt In Temporary Housingcontrasting
confidence: 51%
“…Therefore, the high prevalence of DVT may have resulted from the different types of imaging methods used when compared with the prevalence detected by proximal imaging. However, we still emphasized distal imaging because lethal thromboemboli may occur in proximal veins as a result of proximal propagation from calf DVT . In addition, isolated distal DVT was significantly more often associated with transient risk factors (recent surgery, recent plaster immobilization, and recent travel), whereas proximal DVT was significantly more often associated with chronic health states (active cancer, congestive heart failure, or respiratory insufficiency, and age of >75 years) .…”
Section: Discussionmentioning
confidence: 99%
“…Kageyama et al [28] and Ro and Kageyama [29] reported that the soleal vein contains over 10 multibranched veins in each leg and they are roughly subclassified into three groups: (1) centralis, (2) medialis, and (3) lateralis.…”
Section: Discussionmentioning
confidence: 99%
“…5 The current studies found that venous wall injury, blood stagnation, and hypercoagulable state are the main risk factors of DVT. [6][7][8] Evidence supported that coagulation factors contribute to wound repair after tissue injury and wound injuries, and the activation of coagulation system may be an important role in DVT occurrence. 9 In recent years, the association of gene polymorphisms and DVT formation has been increasing recognized as an attracting topic.…”
Section: Introductionmentioning
confidence: 99%